Improving The Competency and Performance of Dadaprejo Village Offices Through Effective Human Resources Management and Public Services - Ali Hanafiah; Ervita Nindy Oktoriani; Iqbal Rulliasyah; Farah Adiba (Universitas Muhammadiyah Palembang, 2025)
This community service activity aimed to improve the competence and performance of the officials of Dadaprejo Urban Village through strengthening human resource management and the implementation of effective public services. The activity was carried out face-to-face in October 2025 with 25 participants consisting of village officials and staff. The methods used included training, discussion, and interactive lectures on public service ethics, digital-based management, and performance evaluation. The results showed an increase in participants’ understanding of the principles of effective public services and human resource management. The participants were able to identify strategies to improve their performance and service delivery. Although no follow-up evaluation had been conducted, the activity successfully built awareness of the importance of competence and integrity in providing public services.